Copy number loss of KDM5D may be a predictive biomarker for ATR inhibitor treatment in male patients with pulmonary squamous cell carcinoma - Ayako Ura; Takuo Hayashi; Kazumasa Komura; Masaki Hosoya; Kazuya Takamochi; Eiichi Sato; Satomi Saito; Susumu Wakai; Takafumi Handa; Tsuyoshi Saito; Shunsuke Kato; Kenji Suzuki; et al. (The Journal of Pathology: Clinical Research, 2024)
Abstract A limited number of patients with lung squamous cell carcinoma (SCC) benefit clinically from molecular targeted drugs because of a lack of targetable driver alterations. We aimed to understand the prevalence and clinical significance of lysine‐specific demethylase 5D (KDM5D) copy number loss in SCC and explore its potential as a predictive biomarker for ataxia‐telangiectasia and Rad3‐related (ATR) inhibitor treatment. We evaluated KDM5D copy number loss in 173 surgically resected SCCs from male patients using fluorescence in situ hybridization. KDM5D copy number loss was detected in 75 of the 173 patients (43%). Genome‐wide expression profiles of the transcription start sites (TSSs) were obtained from 17 SCCs, for which the cap analysis of gene expression assay was performed, revealing that upregulated genes in tumors with the KDM5D copy number loss are associated with ‘cell cycle’, whereas downregulated genes in tumors with KDM5D copy number loss were associated with ‘immune response’. Clinicopathologically, SCCs with KDM5D copy number loss were associated with late pathological stage (p = 0.0085) and high stromal content (p = 0.0254). Multiplexed fluorescent immunohistochemistry showed that the number of tumor‐infiltrating CD8+/T‐bet+ T cells was lower in SCCs with KDM5D copy number loss than in wild‐type tumors. In conclusion, approximately 40% of the male patients with SCC exhibited KDM5D copy number loss. Tumors in patients who show this distinct phenotype can be ‘cold tumors’, which are characterized by the paucity of tumor T‐cell infiltration and usually do not respond to immunotherapy. Thus, they may be candidates for trials with ATR inhibitors.